Long-term (1970-2017) temporal trends of polychlorinated biphenyls in fish, settling material, and sediments from populated and remote sites in Río de la Plata estuary, Argentina - Colombo, Juan Carlos (2018)
Temporal trends of polychlorinated biphenyls (PCBs) were studied for detritivorous fish (1996-2017) and settling material (2002-2017) from polluted Buenos Aires coast and for a dated sediment core (1970-2013) from the outer Río de la Plata estuary. In spite of contrasting concentrations [5.3 ± 6.3 μg·g -1 dry weight (dw) for fish, 48 ± 26 ng·g -1 dw for settling material, and 1.5 ± 0.7 ng·g -1 dw for core], all three revealed exponentially decreasing trends over time (97%, 83%, and 83%, respectively). Time trends showed peak maxima coincident with Argentina's period of maximum PCB usage in 1973-1980 (80 cm depth in the core) and pulse discharges related to PCB banning in 2001-2002 (fish) with a lighter signature enriched in less persistent tri- and tetrachlorobiphenyls. The log-linear PCB time trends compare well with the predicted decrease for a high emission scenario from global emission data; the best fit was observed for the less impacted sediment core (-2%·year -1 versus -3%·year -1 for emission scenario). Steeper slopes are observed for the more polluted settling material (-5%·year -1 ) and especially for fish, in which the background decline trend tripled after the 2001 PCB pulse (from -7%·year -1 to -21%·year -1 ). These PCB time trends in related environmental compartments from contrasted sites provide rare evidence for evaluating the effectiveness of control measures in southern South America.